Pengaruh Model Problem Based Learning Terhadap Peningkatan Kemampuan Penalaran Matematis Siswa Kelas IX SMPN 1 Kalianda - Abyan, Ramzi; Gunowibowo, Pentatito; Widyastuti (FKIP Universitas Mataram, 2025)
Thisl researchl aims tol determinel thel effect ofl thel Problem Basedl Learningl modell on improving lstudents' mathematicall reasoning abilities. The populationl in thisl study wasl alll students inl class IX ofl SMPl Negeril 1 Kalianda, odd lsemester of the 2023/2024 academicl year, distributed in ten classes, namely IX.1 to IX.10, heterogeneously. Samplingl was carriedl out usingl a clusterl random samplingl technique, andl 30 studentsl in classl IX.1 were selected asl the experimentall class andl 30 studentsl in lclass IX.2 were selected asl the controll class. Thel research designl used wasl a lpretest-posttest controll group ldesign. This researchl data isl in thel form ofl quantitative datal obtained froml tests of students' mathematical reasoningl abilities. Basedl on thel results lof research using lthe Mann-Whitneyl U ltest, it wasl found thatl the increasel in lstudents' mathematical reasoning abilitiesl in thel experimental classl was higher than thel increasel in lstudents' mathematical reasoningl abilities inl thel controll class. Basedl on this, itl can bel concluded thatl the Probleml Based Learningl model has anl effect onl improving students' mathematical reasoning abilities.